Determining appropriate stiffness levels for spudcan foundations using jack-up case records - Cassidy, M; Hoyle, M; Houlsby, G; Marcom, MR (2002)
The level of soil stiffness under spudcan footings is an area of intense interest and debate, with many practitioners believing that current jack-up assessment guidelines are overly conservative. In order to evaluate appropriate stiffness parameters, back-analysis of case records of jack-up platforms in the North Sea has been performed. The records relate to three different rigs at a total of eight locations, which include a variety of soil conditions, water depths and sea-state severity. For each site the horizontal deck displacements and the sea-state conditions under storm loading are available. Numerical simulation of the platforms under storm loading was undertaken with varying levels of foundation stiffness. For each set of stiffness one-hour of numerical simulation was performed, with the most severe recorded environmental loading conditions for that site used. The horizontal deck displacements of the measured data and the numerical simulation results have been compared in both the frequency domain and by the magnitude of response. On the basis of the analyses, recommendations can be made for higher stiffness factors then are currently suggested in the SNAME, 1997 Technical and Research Bulletin 5-5A, Site Specific Assessment of Mobile Jack-up Units (SNAME, 1997).